Interfaces entre condições psicossocioambientais e qualidade de vida no município de Propriá-SE - Siqueira, Thiago Santos (2017)
The objective of this research is to analyze the psychosocialenvironmental conditions of the municipality of Propriá-SE, in order to promote ways of existence that favor environmental preservation and the consequent improvement of the quality of life of the population. Was discussed in this study the interfaces between psychosocial and environmental conditions and quality of life in the city of Propriá-SE, a region characterized by potentialities to be developed in social, economic, cultural and mainly environmental areas. The methodological procedure used instruments that provided information on the historical-geographical space and on the other that provided information on the psychosocial and environmental conditions and quality of life of the population of Propriá. In addition to these instruments, the participant observation was used to compare the data obtained through the instruments with the reality observed in the field and to identify the social actors, institutions and places relevant to the study. This methodology allowed to verify that there is a connection between the psychosocialenvironmental conditions of the municipality of Propriá and the quality of life of the population. In addition, it showed that the modes of existence (behaviors, beliefs, attitudes and values) that favor environmental preservation and result in the improvement of the quality of life of the population. Based on these aspects, it becomes possible to subsidize the elaboration of projects of extension of the Federal Institute of Sergipe (IFS) in the municipality of Propriá that allow the Sustainable Development of this locality and consequently better environmental conditions and quality of life for the population. Finally, it is believed that the results of this study will meet the psychosocial and environmental demand of the region with a view to the formulation and implementation of Sustainable Development Policies.